A linear 2D-conjugated polymer based on 4, 8-bis(4-chloro-5-tripropylsilyl-thiophen-2-yl)benzo[1, 2-b:4, 5-b′]dithiophene (BDT-T-SiCl) for low voltage loss organic photovoltaics. Issue 18 (5th April 2022) - Zhou, Jialing; Lei, Peng; Geng, Yanfang; He, Zehua; Li, Xianda; Zeng, Qingdao; Tang, Ailing; Zhou, Erjun
Abstract : Organic photovoltaics (OPVs) are a promising technology for indoor low-energy-consumption portable electronic equipment. Abstract : Organic photovoltaics (OPVs) are a promising technology for indoor low-energy-consumption portable electronic equipment. However, the relatively large voltage loss ( V loss ) of OPVs, typically exceeding 0.6 V, limits their application. Here, we develop a wide bandgap (WBG) two-dimensional (2D) linear polymer PE6 with a donor–π–acceptor (D–π–A) backbone structure, where 4, 8-bis(4-chloro-5-tripropylsilyl-thiophen-2-yl)benzo[1, 2- b :4, 5- b ′]dithiophene (BDT-T-SiCl), thienothiophene (TT) and benzo[ d ][1, 2, 3]triazole (BTA) are used as the D, π and A units, respectively. PE6 achieves a power conversion efficiency (PCE) of 15.09% when blended with a narrow-bandgap acceptor Y6 ( E g = 1.33 eV), which is one of the highest values in BTA-based photovoltaic polymers. In addition, using classic IT-M (a medium-bandgap acceptor, E g = 1.60 eV) and BTA3 (a wide-bandgap acceptor, E g = 1.82 eV) as acceptors, PE6 -based OPVs exhibit a high V OC of 1.032 V and 1.292 V, respectively. Notably, the V loss in the three combinations is in the range of 0.54∼0.57 V, and the non-radiative voltage loss in the PE6 :BTA3 blend is as low as 0.158 V. Therefore, our results indicate that introducing both silicon and chlorine atoms simultaneously on the 2D conjugated side chain is effective to design photovoltaic polymers with decreasing V loss . In addition, PE6 has the potential as a standard polymer to pair with different types of newly developed non-fullerene acceptors (NFAs).